Global dimensions of intellectual property rights in science and technology - Wallerstein, Mitchel B.; Mogee, Mary Ellen; Schoen, Roberta A. (National Academy Press, 1993)
Annotation This volume offers an update on current international intellectual property rights (IPRs) negotiations and includes case studies on software, computer chips, optoelectronics, and biotechnology. The volume covers these and other issues: (1) Modern economic theory as a basis for approaching international IPRs; (2) U.S. intellectual property practices versus those in Japan, India, the European Community, and the developing and the newly industrializing countries; (3) Pros and cons of a uniform international IPRs regime versus a system reflecting national differences. Index. Approx.